Measuring Up : New Directions for Environmental Programs at the World Bank - Buys, Piet; Dasgupta, Susmita; Meisner, Craig; Pandey, Kiran; Wheeler, David R.; Bolt, Katharine; Hamilton, Kirk; Wang, Limin (World Bank, Washington, DC, 2014)
The World Bank's new environment strategy advocates cost-effective reduction of air and water pollutants that are most harmful to human health. In addition, it addresses threats to the livelihood of over one billion people who live on fragile lands-lands that are steeply sloped, arid, or covered by natural forests. The new approach will require accurate information about environmental threats to health and livelihood, as well as an appropriate resource-allocation strategy. Drawing on recent research at the World Bank and elsewhere, this paper attempts to apply an optimal investment approach. It develops a rule for optimal cross-country resource allocation that reflects the Bank's investment policy. Using this rule, the paper estimates optimal country shares of the Bank's environmental investments from two sets of variables: threats from outdoor air pollution, water pollution, and fragile lands; and estimates of the likelihood that Bank projects will succeed. The paper combines the country shares with the Bank's investment data to estimate optimal country allocations for each environmental problem. Finally, it aggregates the country results to allocations for the major regions in which the Bank operates. Combining optimal investments for pollution and fragile lands, it finds that the largest share of total investment goes to East Asia (44 percent), followed by South Asia (21 percent) and Sub-Saharan Africa (19 percent). Other regions get significantly lower shares.